ANALISIS PENGGABUNGAN PERKARA GUGATAN GANTI KERUGIAN DALAM PERADILAN MILITER - Destri Prasetyoandi (Universitas Borneo Tarakan, 2021)
Military Judicial is a mechanism for justice seekers to carry out efforts against what they have experienced in a criminal act involving Soldiers or Military Members. As a judiciary, the Military Court is also equipped with the authority to examine and decide upon an application for combination of compensation lawsuits cases submitted by victims or parties who feel aggrieved.The combination of compensation lawsuit cases is regulated in Article 183 Law Number 31 of 1997 concerning Military Courts. If an act which forms the basis of an indictment in a criminal case examination by the Military Court / High Military Court causes harm to another person, the Chief Judge at the request of the person who feels aggrieved may decide to combine the compensation lawsuit cases with his criminal case.Regarding the combination of these cases, mechanisms that are generally regulated by law must be implemented properly in order to not cause uncertainty or loss for the parties in litigation. Likewise, with regard to the legal status, if the decision is filed for appeal, it is necessary to consider the legal consequences regarding criminal and civil decisions. The existence of the provisions of Article 185 paragraph (1) of Law Number 31 of 1997 concerning Military Courts can be hesitancy for parties in a case considering that each of the decisions that are combined cannot stand alone and must go through the stage of appeal simultaneously, if the criminal verdict is an appeal submitted by both the military prosecutor and the defendant.